Case of Recovery of a Child with Malignant Fibrous Histiocytoma - V.K. Litovka; K.V. Latyshov; Ye.V. Litovka; G.N. Turpakova (Zaslavsky O.Yu., 2012)
Malignant fibrous histiocytoma of soft tissues is extremely rare in children. Clinical case of malignant fibrous histiocytoma of soft tissues in 8-year-old child is described. After complex treatment the child has recovered.